2011
DOI: 10.2147/ceor.s14404
|View full text |Cite
|
Sign up to set email alerts
|

Transferability of health technology assessments and economic evaluations: a systematic review of approaches for assessment and application

Abstract: Background:Health technology assessments (HTA) generally, and economic evaluations (EE) more specifically, have become an integral part of health care decision making around the world. However, these assessments are time consuming and expensive to conduct. Evaluation resources are scarce and therefore priorities need to be set for these assessments and the ability to use information from one country or region in another (geographic transferability) is an increasingly important consideration.Objectives:To revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 12 publications
2
88
0
5
Order By: Relevance
“…Thirty-nine percent of respondents indicated that there were no guidelines for conducting HTA in their countries, but 11% did not answer this question. Sixty-two percent said they used HTA reports that had been produced in other jurisdictions to help in their decisions, which agrees with findings from other authors (15)(16)(17)(18)(19)(20)(21). HTA work produced in different contexts is usually adapted to the local situation in order to be used in the decision-making process.…”
Section: Discussionsupporting
confidence: 80%
“…Thirty-nine percent of respondents indicated that there were no guidelines for conducting HTA in their countries, but 11% did not answer this question. Sixty-two percent said they used HTA reports that had been produced in other jurisdictions to help in their decisions, which agrees with findings from other authors (15)(16)(17)(18)(19)(20)(21). HTA work produced in different contexts is usually adapted to the local situation in order to be used in the decision-making process.…”
Section: Discussionsupporting
confidence: 80%
“…However, the additional money spent on EVH can be considered 'good value for money' as our analysis showed that EVH is cost-effective compared to OVH from the Danish healthcare system's perspective. To assess whether this result is transferable to other jurisdictions it is ideal to perform a formal evaluation using one of several tools to assess transferability [23][24][25]. It should be noted that the decision analytic model was informed with data from a meta-analysis which included published data from a variety of countries and that the results of the present economic evaluation therefore is likely to be generalizable to a number of jurisdictions.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, apesar dos progressos na identificação de fatores críticos e não críticos para a transferibilidade das evidências econômicas, a identificação de uma lista extensa de fatores e as abordagens para a transferibilidade que envolvem uma complexa identificação dos pesos para cada um deles trazem incerteza sobre a praticidade e utilidade dos métodos desenvolvidos até o momento para considerações futuras sobre transferibilidade (Goeree et al, 2011).…”
Section: Generalização E Transferibilidade De Evidências Econômicasunclassified